The prognosis of pulmonary arterial hypertension associated with primary Sjögren's syndrome: a cohort study. (June 2018) - Liu, Z; Yang, X; Tian, Z; Qian, J; Wang, Q; Zhao, J; Huang, C; Liu, Y; Guo, X; Wang, H; Lai, J; Li, M; et al.
Pulmonary arterial hypertension (PAH) is a rare and severe complication of primary Sjögren's syndrome (pSS). Cohort studies indicate that the underlying diseases of PAH associated with connective tissue disease (CTD-PAH) in Asian countries are different from that in the United States and in Europe. This study investigated the clinical characteristics, survival, and prognostic factors of pSS-PAH in Chinese patients. We enrolled 29 patients with pSS-PAH who visited our referral center during August 2007 and May 2015. PAH was confirmed by right heart catheterization (RHC). Baseline demographic data, clinical manifestations, laboratory tests, autoantibody results, hemodynamics data, and treatment regimens were analyzed. All patients were followed up at the Department of Rheumatology, Peking Union Medical College Hospital (PUMCH) every three to six months. All patients were female. Mean age of pSS onset was 34.4 ± 11.1 years. Mean age of PAH diagnosed by RHC was 40.6 ± 9.0 years. There was no significant difference in age, disease duration, and hemodynamic findings between the survivors and the non-survivors in this cohort. The overall one-, three-, and five-year survival rates were 80.2%, 74.8%, and 67.4%, respectively. Prognostic factors of mortality were time between pSS onset and PAH onset (HR 1.102, 95% CI 1.017–1.185, p = 0.018) and cardiac index < 2 l/min/m 2 (HR 5.497, 95% CI 1.063–28.434, p = 0.042). In contrast, the use of immunosuppressants (HR 0.110, 95% CI 0.024–0.495, p = 0.004) was related to better survival. This study demonstrates that the predictors of mortality in patients with pSS-PAH include delayed onset of PAH in pSS and worse cardiac function. Immunosuppressants can improve the prognosis of pSS-PAH.